Improving marketing communications : Case: Construction Company Karjalan Rakennus ja Maalaus Ltd. - Korhonen, Tatiana (Mikkelin ammattikorkeakoulu, 2014)
The developments in the holiday home purchases in South Eastern Finland started in 2005 are characterized by the significance of the Russian citizens as potential buyers. This has made the region lucrative for individual holiday property and holiday village building, thus increasing the competition among the companies offering ready-to-move houses and construction services. The objective of the thesis was to research how to improve marketing communications for the small construction company Karjalan Rakennus ja Maalaus Ltd. towards Russian customers. The focus was kept on the individual customers buying high-quality holiday property and those who might be interested in investing in cottage villages in South Savo and South Karelia. Along with thorough examination of conventional theories of marketing communication tools, the theoretical part includes discussion of marketing practices in SMEs and in the construction business. The qualitative research was implemented by studying the current marketing communications of the company, the buyer’s purchase decision making process and tools applicable for utilization in the small enterprise. The data collection methods included semi structured interviews with the company’s owner-manager and two previous buyers of the holiday homes. In order to identify the possible marketing communication channels, a systematic review of Internet sources with elements of benchmarking was carried out. The results showed that Karjalan Rakennus ja Maalaus Ltd. should focus on creating awareness among the prospects. In the outcomes the information about the two cases of the holiday home purchase process from the customer’s point of view was presented. Several communication channels and a list of potential partners which can contribute to awareness of the company were suggested. Practical recommendations for the improvement of the company’s website utilization were developed and visually demonstrated. Proposals for further considerations were prepared based on the side results evolved during ...